Biostimulants : effects on root development in barley (Hordeum vulgare) - Lilliehöök, Alexander (SLU/Dept. Of Plant Biology, 2022)
The use of biostimulants has increased greatly in the last 20 years. In year 2012 over 6 million hectares in Europe was treated with biostimulants and the market is expected to almost double in the coming 5 years compared to present levels. Biostimulants are used in a wide range of crops and new biostimulant products are continuously appearing on the market. The effect of the biostimulants is often debated but sales agencies promote their products intensely as yield increasing and profitable. This thesis aimed to study the effect of four different biostimulants on the root development of barley (Hordeum vulgare) and to investigate if root development has any correlation with grain yield. The four products tested were Physiolith, Demetias V, Stimplex and Quantis. Stimplex and Demetias V are based on seaweed extracts while Quantis is produced by fermentation of sugar cane and Physiolith is based on aminopurins. To study the root development, root samples were collected in barley field trials at two locations (Örberga and Borgeby, Sweden) that had been treated with the biostimulants. The samples were flushed clean from soil and analysed for length, fresh weight and dry weight. Grain yield data was later acquired when the trial plots were harvested. The results showed very small differences between the biostimulants and the control. The only significant results found were for root length where Stimplex and Quantis treated plants showed approximately 7 % longer roots than the control. Noticeable was that there were no significant differences in grain yield between the tested biostimulants and the control, and that the increased root length from Stimplex and Quantis did not seem to affect the grain yield. The results of this study are well in line with investigations showing that biostimulants tested under field conditions may not reach expectations of improved crop properties raised from tests conducted in controlled environments